A Structural Equation Model of Loyalty to LANNA Cultural Tourism in Northern Thailand - Prakobpol , Tanawut (Metallurgical and Materials Engineering, 2025)
The purposes of this research were: 1) to formulate a model of structural equation of loyalty to evaluate Lanna cultural tourism in the northern part of Thailand; 2) to evaluate alongside empirical data how consistent the model is in relation to Lanna cultural tourism in the northern part of Thailand and; 3) to investigate the direct and indirect impacts of the model on loyalty seen in the northern region of Thailand for Lanna cultural tourism. The study utilizes a qualitative and quantitative approach which started with interviewing eight people who are government tourism representatives and distributed a survey of 480 people tourists who have visited various Lanna cultural attraction areas in the northern region of Thailand. Descriptive analysis, factor analysis, correlation analysis and structural equation modeling were the methods used to analyze collected data. This led to results highlighting positive correlations between psychological factors and tourism experiences, and between the experiences and destination loyalty. It is for this reason that the results demonstrate that other factors such as tourist’s psychological perception and tourist experience are significantly influential in the directive to loyalty. The findings implication that sustainable development to enhance the region's image should be implemented to promote cultural tourism.